Search engine optimization : an hour a day - Grappone, Jennifer; Couzin, Gradiva (Wiley Publishing, 2011)
"The third edition of the bestselling guide to do-it-yourself SEO Getting seen on the first page of search engine result pages is crucial for businesses and online marketers. Search engine optimization helps improve Web site rankings, and it is often complex and confusing. This task-based, hands-on guide covers the concepts and trends and then lays out a day-by-day strategy for developing, managing, and measuring a successful SEO plan. With tools you can download and case histories to illustrate key points, it?s the perfect solution for busy marketers, business owners, and others whose jobs include improving Web site traffic. A successful SEO plan is vital to any business with an online presence This book provides strategies for setting goals and gaining corporate support, developing and implementing a plan, and monitoring trends and results Offers hints, tips, and techniques for everyone from one-person shops to Fortune 500 companies Companion Web site includes downloadable tracking spreadsheets, keyword list templates, templates for checking rank and site indexes, and a calendar with daily SEO tasks that you can import into your own calendar system Fully updated and expanded, Search Engine Optimization: An Hour a Day, Third Edition will help you raise your visibility on the Web."--Provided by publisher